Combining ablative radiotherapy and anti CD47 monoclonal antibody improves infiltration of immune cells in tumor microenvironments. - Elham Rostami; Mohsen Bakhshandeh; Haniyeh Ghaffari-Nazari; Maedeh Alinezhad; Masoumeh Alimohammadi; Reza Alimohammadi; Ghanbar Mahmoodi Chalbatani; Ehsan Hejazi; Thomas J Webster; Jalil Tavakkol-Afshari; Seyed Amir Jalali (PLoS ONE, 2022)
Radiotherapy as an anti-tumor treatment can stimulate the immune system. However, irradiated tumor cells express CD47 to escape the anti-tumor immune response. Anti- CD47 Immunotherapy is a possible way to tackle this problem. This study evaluated the effect of single high dose radiotherapy combined with an anti-CD47 monoclonal antibody (αCD47 mAb) in CT26 tumor-bearing BALB/c mice. We assessed the tumors volume and survival in mice 60 days after tumor implantation. Also, immune cell changes were analyzed by flow cytometry in tumors, lymph nodes, and spleen. Combination therapy enhanced the anti-tumor response in treated mice by increasing CD8+ T cells and M1 macrophages and decreasing M2 macrophages and myeloid-derived suppressor cells (MDSCs) in the tumor microenvironment (TME). Also, our results showed that combination therapy increased survival time in mice compared to other groups. Furthermore, tumor volumes remarkably decreased in mice that received a single high dose RT plus αCD47 mAb. In conclusion, we showed that combining RT and αCD47 mAb improved the immune cell population in TME, regressed tumor growth, and increased survival in tumor-bearing mice.